The Role of Organic Farming in Hungary and in the Northern Plain Region - Szép, Attila (Acta Agraria Debreceniensis, 2005)
In 2003, the area, which was monitored according to the requirement of organic farming, was 116 thousand hectares in Hungary, and included almost 1700 works, which produce organic products. This is some 2% of the cultivated land of Hungary. The increase of organic farming areas has slowed down in recent years. In these conditions the optimal 300,000 hectares cannot be achieve in 2006.In 2003, the area which was cultivated according to the regulations of organic farming was more than 33 thousand hectares in the North Great Plain Region, and monitored 250 enterprises the associates of the monitor organization. The challenge of the coordinators of the organic farming in the region are to fortificate the processing industry. The goal is to increase the added value of the products.